Penerapan Metode Tartili Daiam Pembelajaran Membaca Al-Qur’an Di TPQ Nurul Hikmah Kertonagoro Jenggawah Jember - Fikri Farikhin (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2022)
Abstract: The purpose of this study is to describe the implementation of the Tartili method in learning to read the Qur'an at TPQ Nurul Hikmah Kertonegoro Jenggawah Jember. This thesis is a descriptive qualitative field research, namely a method that describes the results of research in the field by means of objective rational thinking, therefore the data is collected through observation, interviews, and documentation, while the data analysis uses data reduction. The general conclusion in writing this thesis is that the implementation of the Tartili method in TPQ Nurul Hikmah Kertonegoro Jenggawah Jember has produced children who are able to read the Koran fluently, well and correctly, and students are able to understand the rules of reading the Koran that is read. Keywords: Tartili Method, al-Qur’an Learning